Urban Popular Economies - Benjamin, Solomon; Castronovo, Alioscia; Cavallero, Luci; Cielo, Cristina; Gago, Véronica; Guma, Prince; Gupte, Rupali; Habermehl, Victoria; Salman, Lana; Shetty, Prasad; Simone, AbdouMaliq; Smith, Constance; et al. (Public Culture, 2022)
What is a life worth living and how is it concretely actualized by an urban majority making often unanticipated, unformatted uses of the urban to engender livelihoods in a dynamic and open-ended process? This is the key question undertaken in this collectively written piece. This means thinking about work, paid and unpaid, in ways that highlight the everyday practices of urban inhabitants as they put together territories in which to operate, which sustain their imaginations of well-being as part of a process of being with others—in households, neighborhoods, communities, and institutions. What is it that different kinds of workers have in common; what links them; where does the household begin and end; what is the difference between productive and reproductive work?
EPrint Processing Status: Full text deposited in DRO